Morbidly adherent placenta at extreme prematurity: can major haemorrhage and hysterectomy be prevented? - Shafiee MN,; Lim PS,; Rahana AR,; Nor Azlin MI,; Wan Faraliza ZA,; Isa MR,; Mohd Hashim O, (Department of Surgery, UKM Medical Centre, 2011)
Morbidly adherent placenta with spontaneous rupture of membrane at extreme prematurity poses poor pregnancy outcome. Various issues on different management modalities still remain perplexed and individual consideration is vital. Two cases of morbidly adherent placenta with symptomatic per vaginal bleeding and spontaneous rupture of membrane at severe prematurity were reviewed and discussed. We found that, active intervention by termination of pregnancy and methotrexate therapy at early gestation can prevent the need of hysterectomy following major obstetrics haemorrhage.